Plasma Leukocyte Cell-Derived Chemotaxin 2 (LECT2) as a Risk Factor of Coronary Artery Disease: A Cross-Sectional Study. (March 2022) - Wei, Mengqiu; Liu, Jun; Pan, Hailin; Zhou, Ziting; Guo, Kai
Many studies have shown that leukocyte cell-derived chemotaxin 2 (LECT2) is associated with metabolic disorders, which is a risk factor of arteriosclerosis. We assessed the level of LECT-2 in patients with coronary artery disease (CAD) and its severity and prognosis. We selected 666 participants who underwent coronary angiography in our hospital and included patients with non-CAD, patients with stable angina pectoris (SAP), patients with unstable angina (UA), patients with non-ST-segment elevation myocardial infarction (NSTEMI) and patients with ST-segment elevation myocardial infarction (STEMI). The serum level of LECT-2 was higher in patients with CAD than in patients with non-CAD and was an independent predictor for CAD. Subgroup analysis showed that compared with the SAP group, the UA, NSTEMI, and STEMI groups had higher serum levels of LECT-2. In addition, the level of LECT-2 was related to the SYNTAX score and SYNTAX II score. Finally, patients with acute myocardial infarction (AMI) with elevated levels of LECT-2 had a higher risk of major adverse cardiovascular events (MACEs) within 12 months than those with lower levels of LECT-2. Plasma LECT-2 levels may be useful for the diagnosis of CAD and as predictors of MACE in patients with AMI.